Amyloid-β Peptide Impact on Synaptic Function and Neuroepigenetic Gene Control Reveal New Therapeutic Strategies for Alzheimer’s Disease - Karisetty, Bhanu Chandra; Bhatnagar, Akanksha; Armour, Ellen M.; Beaver, Mariah; Zhang, Haolin; Elefant, Felice (Frontiers in Molecular Neuroscience, 2020)
Amyloid-β (Aβ) peptides can form protease-resistant aggregates within and outside of neurons. Accumulation of these aggregates is a hallmark of Alzheimer's disease (AD) neuropathology and contributes to devastating cognitive deficits associated with this disorder. The primary etiological factor for Aβ aggregation is either an increase in Aβ production or a decrease in its clearance. Aβ is produced by the sequential activity of β- and γ-secretase on the amyloid-β precursor protein (APP) and the clearance is mediated by chaperone-mediated mechanisms. The Aβ aggregates vary from soluble monomers and oligomers to insoluble senile plaques. While excess intraneuronal oligomers can transduce neurotoxic signals into neurons causing cellular defects like oxidative stress and neuroepigenetic mediated transcriptional dysregulation, extracellular senile plaques cause neurodegeneration by impairing neural membrane permeabilization and cell signaling pathways. Paradoxically, senile plaque formation is hypothesized to be an adaptive mechanism to sequester excess toxic soluble oligomers while leaving native functional Aβ levels intact. This hypothesis is strengthened by the absence of positive outcomes and side effects from immunotherapy clinical trials aimed at complete Aβ clearance, and support beneficial physiological roles for native Aβ in cellular function. Aβ has been shown to modulate synaptic transmission, consolidate memory, and protect against excitotoxicity. We discuss the current understanding of beneficial and detrimental roles for Aβ in synaptic function and epigenetic gene control and the future promising prospects of early therapeutic interventions aimed at mediating Aβ induced neuroepigenetic and synaptic dysfunctions to delay AD onset.